Identifikasi Kecemasan Mahasiswa Kebidanan terhadap Pembelajaran Daring dalam Masa Pandemi COVID-19 - Dian Furwasyih; Yulia Arifin; Nur Femi (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
The COVID-19 pandemic has caused many social problems for the community, including students. Students who are teenagers must adapt to the online learning system. Adolescents experience anxiety in the form of academic pressure, anxiety that they cannot follow online learning well, the task load is felt to be piling up, online learning is not effective because there is no direct interaction with lecturers, and so on. This quantitative descriptive study was designed to identify anxiety in students of the Diploma III Midwifery Study Program and Midwifery Study Program Undergraduate Program and Midwifery Professional Education Program STIKes MERCUBAKTIJAYA Padang. A modified questionnaire from the Hamilton Anxiety Rating Scale (HARS) form was distributed in google form to 138 Midwifery students. Data were analyzed using SPSS. The results showed that almost half of the respondents (42%) were 19 years old, almost half (47.8%) were in semester 2 or level 1. More than half (53.6) of students lived in boarding houses, with adequate internet network conditions by 61.6%. More than half (59.4%) of students stated that they were quite capable of doing assignments with computers and 63.7% stated that online learning was not effective. More than half of the respondents (54.3%) had a moderate level of anxiety in dealing with online learning during the COVID-19 pandemic. This anxiety can be reduced by providing various counseling services such as individual counseling services, guidance and group counseling. Universities must be able to facilitate this with teleconsultation services with academic advisors and psychologists if needed if student anxiety adversely affects learning outcomes and causes disturbances to students' mental health.